Extraction of bisphenol F three isomers from water with 1‐octyl‐3‐methylimidazolium tetrafluoroborate ionic liquid. (9th November 2016) - Pan, Langsheng; Pan, Lifang; Wang, Tiantian; Wang, Zhi; Wu, Zhimin; Li, Yongfei; Zuo, Cuncun; Liu, Yuejin
Abstract : The extraction for three isomers of bisphenol F (BPF) was studied in a hydrophobic ionic liquid/water biphasic extraction system. The influences of some factors, such as ionic liquid structure, phase ratio, temperature, pH value, and NaCl concentration on the extraction of BPF three isomers were investigated, and excellent efficiency with more than 99.0 % extraction efficiency was obtained using 1‐octyl‐3‐methylimidazolium tetrafluoroborate ([Omim][BF4 ]) as an extractant. The extraction mechanism of the hydrogen bonds interaction between [Omim][BF4 ] and BPF three isomers were proven by 1 H‐NMR spectrum and the density functional theory (DFT). From the 1 H‐NMR spectrum, the immediate disappearance of the BPF isomer hydroxyl protons upon addition of [Omim][BF4 ] was found, which indicated the existence of hydrogen bond interaction between BPF isomer and [Omim][BF4 ]. Through the computer simulation, the hydrogen bonds strength decreased in the order of 2, 2′‐BPF > 2, 4′‐BPF > 4, 4′‐BPF, which is consistent with the descending order of distribution coefficients obtained through the experiments. These results are promising for the liquid‐liquid extraction and enrichment of phenols in related industrial processes.